Role of the Table Filière Karité in supporting local producers in Burkina Faso - Tapsoba, A.; Zida, M.; Wardell, D.A.; Elias, M. (Center for International Forestry Research, 2022)
Globalization and economic liberalization are affecting how the shea sector is organized and how it operates in shea producing countries. In Burkina Faso, where shea is the country’s fourth largest export, the shea sector is a major source of foreign currency. The sector-wide trade organization Table Filière Karité (Shea Sector Round Table – TFK), which brings together direct stakeholders in the Burkinabe shea sector, supports the development of the sector. Our analysis of the role of TFK in supporting local stakeholders in the sector in the current context of a globalized market and the regulations in force in Burkina Faso has shed light on the challenges that TFK must overcome and opportunities that it could harness to achieve its mission. It is based on information collected through interviews and documentary research.